Pengaruh Model Pembelajaran Missouri Mathematics Project (MMP) Terhadap Kemampuan Pemahaman Konsep Bangun Datar Kelas II MI Miftahul Huda - Mitha Annisa Rachma; Arissona Dia Indah Sari; Arya Setya Nugroho (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research aims to determine the implementation of the Missouri Mathematics Project (MMP) learning model and the influence of the Missouri Mathematics Project (MMP) learning model on the concept understanding ability of class II MI Miftahul Huda students in the 2024/2025 academic year. The method used in this research is an experimental method with a quasi-experimental type. The design in this research is a nonequivalent control group design. This research design involved two classes, the experimental class, namely class II A using the missouri mathematics project learning model and control class II C using the conventional learning model. Data collection techniques use the results of concept understanding tests. Based on the results of research on the Independent Sample T-test which shows that the significance (2-tailed) is 0.000 < 0.05, which means less than 0.05, so H0 is rejected and Ha is accepted, which means there is an influence of the missouri mathematics project learning model on understanding ability. MI Miftahul Huda class II flat shape concept.